Physico-chemical investigation of the volatile oil of Myristica fragrans Houtt. (Fam. Myristicaceae) - Cammayo, Carlos M.
A clear, colorless essential oil which turns to pale yellow upon standing was obtained from the kernels of the dried ripe seed of Myristica fragrans Houtt. at an average yield of 5.73% (v/w). the nutmeg oil gave the following physicochemical constants: specific gravity, 0.8934 (25°C); optical rotation, 34.6435; specific rotation, 40.4230 (28°C); refractive index, 1.4761 (25°C); acid value, insignificant; ester value, 6.0